Experiences and perceptions of stroke survivors and occupational therapists on community reintegration post stroke in the Western Cape - Lindner, Hendrina Cecilia (My University, 2022)
Worldwide, stroke is one of the leading causes of death and disability. In South Africa, despite numerous policies guiding rehabilitation at different levels of care, stroke survivors show poor levels of community reintegration on returning home. The purpose of this study was to explore the lived experiences of stroke survivors on returning home after having received in-patient rehabilitation as well as their perceptions of the barriers and facilitators to their recovery and process of community reintegration. Furthermore, the study explored the barriers and facilitators to facilitate community reintegration perceived by occupational therapists working in the same area when providing services for stroke survivors. A descriptive, qualitative study design with a phenomenological emphasis was used to conduct this study. Demographic questionnaires and semi-structured key informant interviews were used to conduct interviews with eleven stroke survivors who had received in-patient rehabilitation and were one to three years post stroke as well as two occupational therapists servicing the same area. Three themes emerged from the study. The first theme emerged as the changes in occupational performance experienced by stroke survivors. The second and third theme emerged as the barriers and facilitators to community reintegration as perceived and experienced by stroke survivors living in the Eastern Subdistrict of the Western Cape. Data from the occupational therapy participants were used to triangulate the data that emerged from the stroke survivor participant interviews. Community reintegration continues to be a challenge for stroke survivors living in the Eastern Subdistrict of the Western Cape. Often the barriers are social determinants of health such as the environment, poor coordination of rehabilitation services and poor access to public transport. On the other hand, several facilitators such as stroke survivors’ motivation, drive and social support systems were identified occupational therapists can capitalise on to facilitate the process of community reintegration for stroke survivors. The study highlighted the importance of effective discharge and community-based services to ensure the continuum of rehabilitation for stroke survivors when returning home.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022